The Spread of Printing : Eastern Hemisphere: India, Burma, Ceylon - Rhodes, Dennis E., (European History and Culture - Book Archive pre-2000., 1969)
This volume is published as part of the series The Spread of Printing , a history of printing outside Continental Europe and Great Britain. The print edition is available as a set of eleven volumes (9789063000257).